2020
DOI: 10.2337/db20-0070
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Studies of Leptin Concentrations Implicate Leptin in the Regulation of Early Adiposity

Abstract: Leptin influences food intake by informing the brain about the status of body fat stores. Rare LEP mutations associated with congenital leptin deficiency cause severe earlyonset obesity that can be mitigated by administering leptin. However, the role of genetic regulation of leptin in polygenic obesity remains poorly understood. We performed an exome-based analysis in up to 57,232 individuals of diverse ancestries to identify genetic variants that influence adiposity-adjusted leptin concentrations. We identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 54 publications
(29 reference statements)
1
59
1
Order By: Relevance
“…Additionally, our PRS analysis using a T2D reference study finds persistently low BMI during childhood for children in the highest decile of BMI-adjusted T2D PRS, and it is tempting to ascribe these late effects on childhood BMI to mechanisms acting through insulin and glucose metabolism given the numerous studies associating KLF14 with T2D. However, alleles in high LD with the infant BMI and T2D risk increasing alleles were recently associated with lower plasma leptin levels adjusted for BMI 41 , offering a mechanistic hypothesis and yet another putative link between leptin regulation and weight gain in infancy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Additionally, our PRS analysis using a T2D reference study finds persistently low BMI during childhood for children in the highest decile of BMI-adjusted T2D PRS, and it is tempting to ascribe these late effects on childhood BMI to mechanisms acting through insulin and glucose metabolism given the numerous studies associating KLF14 with T2D. However, alleles in high LD with the infant BMI and T2D risk increasing alleles were recently associated with lower plasma leptin levels adjusted for BMI 41 , offering a mechanistic hypothesis and yet another putative link between leptin regulation and weight gain in infancy.…”
Section: Discussionmentioning
confidence: 77%
“…While rs287621 is associated with several adult phenotypes, the strongest known association for rs12672489 is comparative body size at age 10 in the UK Biobank (p < 3.5 × 10 −7 ), showing that this variant influences childhood growth despite residing outside of the region critical for adult traits. eQTL studies have linked variants to the abundance of KLF14 transcript in adipose tissue 40 and a variant near KLF14 has been associated with lower plasma leptin levels 41 , offering a mechanistic hypothesis and yet another putative link between leptin regulation and weight gain in infancy.…”
Section: Resultsmentioning
confidence: 99%
“…Leptin has several endocrine functions, such as appetite regulation, immune and inflammatory response/function, hematopoiesis, angiogenesis, reproduction and bone formation. Mutations in the leptin gene and its regulatory regions can cause severe obesity and are linked to development of type 2 diabetes [ 33 , 34 ]. Godfrey et al [ 14 ] found that the RXRA gene was affected by carbohydrates, as a higher methylation of RXRA chr9:136355885 in cord blood was found to be associated with lower maternal carbohydrate intake.…”
Section: Discussionmentioning
confidence: 99%
“…Only nine variants were detected in Europeans [SNP rs17151919 ( LEP ) was not observed in Europeans], five and six of which attained significance after study-wide correction based on leptin levels unadjusted and adjusted for BMI, respectively. We used the effect sizes for unadjusted leptin levels determined in Europeans calculated with an additive model for our MR. How much of the total variance is explained by the SNPs (h 2 SNP ) was not reported ( Yaghootkar et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%